2008
DOI: 10.2967/jnumed.107.042564
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Need for an Implantable Cardioverter Defibrillator Using Cardiac Metaiodobenzylguanidine Activity Together with Plasma Natriuretic Peptide Concentration or Left Ventricular Function

Abstract: Despite widespread use of implantable cardioverter defibrillators (ICDs), their cost and the fact that only a certain group of patients fully benefits from the devices require appropriate risk stratification of patients. This study investigated whether altered cardiac autonomic function is associated with the occurrence of ICD discharge or lethal cardiac events. Methods: Fifty-four ICD-treated patients were prospectively followed after assessment of cardiac metaiodobenzylguanidine (MIBG) activity, quantified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 24 publications
2
78
2
Order By: Relevance
“…Cardiac 123 I-mIBG imaging is currently indicated for ''scintigraphic assessment of sympathetic innervation of the myocardium in patients with New York Heart Association [NYHA] class II or class III HF and left ventricular ejection fraction [LVEF] B35% … and to help identify patients with lower oneand two-year mortality risks, as indicated by an [HMR] ratio C1.6.'' Nevertheless, much literature suggests a potential broader use, 91 including identification of patients at increased risk of lethal cardiac arrhythmias in the setting of HF, [92][93][94][95] evaluating primary arrhythmic conditions, [96][97][98][99][100] assessing the presence and risk of ischemic heart disease, 101,102 including in situations of hibernating myocardium 103,104 and post-infarction, [105][106][107] evaluating pre-and post-cardiac transplant patients, [108][109][110] identifying diabetic patients at increased risk from cardiac autonomic dysfunction, 111,112 and monitoring toxicity from chemotherapy. 113 However, based on currently available literature, published guidelines, and the FDA package insert, the following indications can be recommended: 114 • For patients with NYHA class II or III heart failure with LVEF B35% to help stratify risk and to promote more informed clinical decision-making when the result of 123 I-mIBG study is likely to influence the decision regarding ICD implant.…”
Section: Tl-201mentioning
confidence: 99%
“…Cardiac 123 I-mIBG imaging is currently indicated for ''scintigraphic assessment of sympathetic innervation of the myocardium in patients with New York Heart Association [NYHA] class II or class III HF and left ventricular ejection fraction [LVEF] B35% … and to help identify patients with lower oneand two-year mortality risks, as indicated by an [HMR] ratio C1.6.'' Nevertheless, much literature suggests a potential broader use, 91 including identification of patients at increased risk of lethal cardiac arrhythmias in the setting of HF, [92][93][94][95] evaluating primary arrhythmic conditions, [96][97][98][99][100] assessing the presence and risk of ischemic heart disease, 101,102 including in situations of hibernating myocardium 103,104 and post-infarction, [105][106][107] evaluating pre-and post-cardiac transplant patients, [108][109][110] identifying diabetic patients at increased risk from cardiac autonomic dysfunction, 111,112 and monitoring toxicity from chemotherapy. 113 However, based on currently available literature, published guidelines, and the FDA package insert, the following indications can be recommended: 114 • For patients with NYHA class II or III heart failure with LVEF B35% to help stratify risk and to promote more informed clinical decision-making when the result of 123 I-mIBG study is likely to influence the decision regarding ICD implant.…”
Section: Tl-201mentioning
confidence: 99%
“…Other studies have evaluated 123I-MIBG imaging for the prediction of VT and SCD. In one of them, H/M resulted as an independent predictor for appropriate ICD therapy; 74 while in the other one WR correlated with higher SCD occurrence. 75 Moreover, studies consistently show that the H/R can reflect response to HF therapies, such as β-blockers 76 or LVADs, 77 as increases in H/R correlate with other clinical or analytical parameters.…”
Section: Sympathetic Activitymentioning
confidence: 99%
“…secondary prevention). Nagahara et al 35 showed that late HMR was a predictor of the occurrence of ICD shock in patients with HF and LVEF < 50% and BNP > 187 pg/ml. When combined with high levels of BNP, HMR < 1.95 had a specificity of 94% and a positive predictive value of 82% for the appropriate use of ICD.…”
Section: Review Articlementioning
confidence: 99%
“…When combined with high levels of BNP, HMR < 1.95 had a specificity of 94% and a positive predictive value of 82% for the appropriate use of ICD. 35 In addition to global cardiac sympathetic activity assessed with 123 I-mIBG scintigraphy, there is evidence that, in ischemic HF, regional innervation/perfusion mismatch with a larger defect size on 123 I-mIBG SPECT than on myocardial perfusion imaging SPECT predisposes to ventricular arrhythmias. [36][37][38] In a large prospective study in 116 CHF patients, eligible for ICD implantation for both primary and secondary prevention of sudden cardiac death (SCD), š²³I-mIBG SPECT was shown to be an independent predictor of appropriate ICD therapy and cardiac death.…”
Section: Review Articlementioning
confidence: 99%